Вавилонский документ о незаконной продаже храмовой рабыни - Дандамаев, M. A.
Dandamajev, M. A.; A Babylonian Document concerning the Illegal Sale of a Temple Slave-Girl; engl. Résumé; Zeit des Kambyses.